2023
DOI: 10.1038/s41467-023-37864-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for activation of CB1 by an endocannabinoid analog

Abstract: Endocannabinoids (eCBs) are endogenous ligands of the cannabinoid receptor 1 (CB1), a G protein-coupled receptor that regulates a number of therapeutically relevant physiological responses. Hence, understanding the structural and functional consequences of eCB-CB1 interactions has important implications for designing effective drugs targeting this receptor. To characterize the molecular details of eCB interaction with CB1, we utilized AMG315, an analog of the eCB anandamide to determine the structure of the AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…These results indicate that the side chains of F180 and W158 are involved in the interaction with BMS-986122, which supports the cryo-EM structure of the MOR(DAMGO)-G i -scFv16 complex in the BMS-986122 bound state. This is further confirmed by a GTP turnover assay that measures the consumption of GTP by G proteins through GTP to GDP turnover 34 36 (Supplementary Fig. 5c ).…”
Section: Resultssupporting
confidence: 54%
“…These results indicate that the side chains of F180 and W158 are involved in the interaction with BMS-986122, which supports the cryo-EM structure of the MOR(DAMGO)-G i -scFv16 complex in the BMS-986122 bound state. This is further confirmed by a GTP turnover assay that measures the consumption of GTP by G proteins through GTP to GDP turnover 34 36 (Supplementary Fig. 5c ).…”
Section: Resultssupporting
confidence: 54%
“…All of the four most potent ligands docked to adopt a "C" shaped conformation characteristic of the experimentally observed geometries of MDMB-Fubinaca 18 , AM11542, and AM841 16 bound to CB1R. Similarly, all four are predicted to hydrogen-bond with S383 7.39 , a potency-determinant interaction at CB1 receptors observed in nearly all agonist-bound ligand-receptor complexes 37,38 .…”
Section: Resultsmentioning
confidence: 70%
“…Additionally, all four ligands are predicted to make secondary hydrogen bonds to H178 2.65 , a feature thought to be important for potency as well as agonism of CB1R 38 . Largely, these electrostatic interactions are made using unique hydrogen-bond acceptor groups, such as an oxazole, oxathiine, or pyridazinone.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier work we demonstrated that this approach can be applied successfully on the AEA scaffold. , Taking this approach, we discovered the first highly potent AEA-like CB1 agonist (AMG315) with resistance to both hydrolytic and oxidative enzymes. Currently AMG315 serves as a valuable tool for in vitro , in vivo , and structural studies. , …”
mentioning
confidence: 99%
“…In an effort to understand the interactions of our key analog AM8125 and 2-AG with the CB1 receptor, we performed molecular docking studies using the available crystal structures of CB1 receptor cocrystallized with the classical cannabinoid agonist AM841 (PDB code 5xr8) and the endocannabinoid agonist AMG315 (PDB code 8ghv). Docking results are shown in Table , while predicted docking poses of the ligands are depicted in Figures and .…”
mentioning
confidence: 99%